PERMASALAHAN PENGUASAAN TANAH TERLANTAR OLEH IPB BOGOR/IPB UNIVERSITY BOGOR YANG DIKUASAI WARGA SELAMA ENAM PULUH LIMA TAHUN TERLETAK DI CILIBENDE RT.002,003,005 RW.002 KELURAHAN BABAKAN KECAMATAN BOGOR TENGAH KOTA BOGOR - Sri Hartini (JPMUJ, 2024)
Based on the 1945 Constitution, Article 33 paragraph 3 states: the earth and the natural resources contained therein are controlled by the state and used for the greatest prosperity of the people. That the residents of Cilibende RT.002, RT.003, and RT.005 RW.002, Babakan Village, Bogor Tengah District, Bogor City control and enjoy, and make use of, the land, for the economic benefit of these residents, some sell, their houses are used as boarding houses by students IPB UNIVERSITY BOGOR Vocational School, so that the land is economically beneficial, and has provided payment of property tax costs to the Bogor City Government, all of which can benefit economically. The theme of the extension is that IPB BOGOR/IPB UNIVERSITY BOGOR will carry out the construction of buildings controlled by Cilibende residents. That IPB BOGOR/IPB UNIVERSITY BOGOR has no legal relationship with the land controlled by Cilibende residents. That the land occupied (Exhibit P-3) every year, the regional government of the city of Bogor has been given living expenses by the residents of Cilibende, by paying Property Tax (PPB), and residents in the Cilibende area of ​​the land have already received a Certificate, so the residents Cilibende.